2000
DOI: 10.1038/74889
|View full text |Cite
|
Sign up to set email alerts
|

Isolating the neural mechanisms of age-related changes in human working memory

Abstract: Working memory (WM), the process by which information is coded into memory, actively maintained and subsequently retrieved, declines with age. To test the hypothesis that age-related changes in prefrontal cortex (PFC) may mediate this WM decline, we used functional MRI to investigate age differences in PFC activity during separate WM task components (encoding, maintenance, retrieval). We found greater PFC activity in younger than older adults only in dorsolateral PFC during memory retrieval. Fast younger subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
366
7
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(420 citation statements)
references
References 27 publications
45
366
7
2
Order By: Relevance
“…The lack of differential frontal activation at posttest indicates that such processing was impaired for the older adults, possibly because of age-related changes in basic processing capacity. Working-memory decline in older age has been linked to reduced dorsal frontal activity (17), and age-related deficits in mental imagery tasks have been related to shrinkage of the prefrontal cortex and decline in working memory (18). Another basic processing resource is speed of mental information processing, and consistent with numerous previous studies (19) we observed pronounced age differences in a test of processing speed.…”
Section: Discussionsupporting
confidence: 78%
“…The lack of differential frontal activation at posttest indicates that such processing was impaired for the older adults, possibly because of age-related changes in basic processing capacity. Working-memory decline in older age has been linked to reduced dorsal frontal activity (17), and age-related deficits in mental imagery tasks have been related to shrinkage of the prefrontal cortex and decline in working memory (18). Another basic processing resource is speed of mental information processing, and consistent with numerous previous studies (19) we observed pronounced age differences in a test of processing speed.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, regardless of the performance differences, correctly performed trials used in the functional analyses produced comparable areas, magnitudes, and group differences in activation across studies. This finding lends confidence to conclusions about compensatory activation in older adults particularly in left prefrontal regions that have been the focus of some debate (DiGirolamo et al, 2001;Jonides et al, 2000;Nielson et al, 2002;Rypma and D'Esposito, 2000). The absence of a behavioral effect in the presence of a functional activation effect between groups could be used to argue that the activation differences between groups are more likely the result of an age effect, and not a performance effect.…”
Section: Discussionmentioning
confidence: 53%
“…More specifically, although the nature of the tasks used to study age-related changes in cognition and neurophysiology within imaging paradigms have varied from facial recognition to verbal working memory, some task nonspecific findings have begun to emerge. Older participants exhibit extraneous areas of activation and greater bilateral activation in functional homologues (i.e., analogous brain regions in the contralateral hemisphere) where younger adults exhibited asymmetrical activation (Cabeza, 2002;Cabeza et al, 1997b;Grady et al, 1994;Madden et al, 1997Madden et al, , 1999Nielson et al, 2002;Schachter et al, 1996, but see Grady et al, 1995;Jonides et al, 2000;Rypma and D'Esposito, 2000). A number of the imaging studies also report differences between younger and older adults in the inferior parietal lobule and the dorsomedial nucleus of the thalamus (DiGirolamo et al, 2001;Grady et al, 1994Grady et al, , 1995Grossman et al, 2001;Madden et al, 1997Madden et al, , 1999Nielson et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…More recent data suggest that the main locus of dysfunction associated with working memory deficits is a more specific region of the PFC -the dorsal lateral PFC (Ref. 38). Research over the last two decades suggests that dopamine modulates how well the PFC makes use of briefly activated cortical representations to circumvent constant reliance on environmental cues and to regulate attention towards relevant stimuli and appropriate responses 20 .…”
Section: Neurobiological Levelmentioning
confidence: 99%